Practical education in our schools - Finlay, T.A. (Statistical and Social Inquiry Society of Ireland, 1906)
It will be admitted as a fundamental principle that the aim of all education is to fit children to do their duty worthily and successfully in later life. This conception of education covers a wide field. It includes the cultivation of the moral and religious sense, as well as the intellectual and physical faculties. We are not concerned here with this wider significance of the term. We confine our attention to that narrower view which regards education as a preparation for the material tasks of life, as the training which fits a man or woman to earn a livelihood, and by so doing to contribute to the general welfare of the community. In this sense only can education be regarded as falling within the competence of the State, or included in its legitimate functions.
Read 5th May, 1905
Keywords: Education, Ireland; 314.15